2021
DOI: 10.3389/fmed.2021.789828
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Step Model for Developing Competency Frameworks in the Healthcare Professions

Abstract: Competency frameworks are developed for a variety of purposes, including describing professional practice and informing education and assessment frameworks. Despite the volume of competency frameworks developed in the healthcare professions, guidance remains unclear and is inconsistently adhered to (perhaps in part due to a lack of organizing frameworks), there is variability in methodological choices, inconsistently reported outputs, and a lack of evaluation of frameworks. As such, we proposed the need for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 41 publications
(89 reference statements)
0
34
0
Order By: Relevance
“…Competency frameworks typically describe professional expectations of healthcare professionals by defining the perceived knowledge, skills, attitudes and other characteristics required to practice safely and effectively (1). They translate professional practice to activities such as assessment, curriculum design and educational frameworks, professional regulation, and clinical specialization (1)(2)(3)(4). Despite this central role they play in developing and regulating professional practice (4), standardized approaches to developing competency frameworks are lacking (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Competency frameworks typically describe professional expectations of healthcare professionals by defining the perceived knowledge, skills, attitudes and other characteristics required to practice safely and effectively (1). They translate professional practice to activities such as assessment, curriculum design and educational frameworks, professional regulation, and clinical specialization (1)(2)(3)(4). Despite this central role they play in developing and regulating professional practice (4), standardized approaches to developing competency frameworks are lacking (5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review found significant variation in methodological approaches to competency framework development; a single, internationally recognized standard was not identified ( 5 ). A six-step model was recently proposed to improve the process, standard, reporting and evaluation of frameworks ( 1 ). While the model identified patients and members of the public as important stakeholders, it did not specify guidance on who, how, or for what purpose(s) to engage them.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of secondary data to gather consumer perspectives may not fully represent their views on the roles and tasks of a dietitian. Competency frameworks should consider involving consumers in their development in the future ( 23 ). However, many of the steps used in this document analysis have been recommended as best practice in competency standards development ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Competency frameworks should consider involving consumers in their development in the future ( 23 ). However, many of the steps used in this document analysis have been recommended as best practice in competency standards development ( 23 ). The positive response received from the profession to early drafts of the standards together with the final product provides reassurance that the process has met user needs.…”
Section: Discussionmentioning
confidence: 99%
“…Competency frameworks provide an outline of the perceived knowledge, skills, attitudes, and other characteristics required to competently enact professional practice within a given context (1). In health professions, these are developed for a number of reasons which can include defining the profession, ensuring a competent workforce, and facilitating curriculum development, systems of assessment, or professional mobility.…”
Section: Introductionmentioning
confidence: 99%